A América do sul e o desenvolvimento sustentável: compromissos para a viabilidade do buen vivir (2016)
The South American continent has been committed to the affirmation of democracy and sustainability due to its cultural integration and the geography of the environment. From the indigenous culture of good living this research has as its general objective to investigate how this proposal can bring other alternatives to the demands for sustainable development in South America that are not covered by European or North American theories. The method used is deductive, along with the technique of bibliographical and documentary research. Finally, there are important adversities to be a worthy life for sustainable development in South America, in the trinomial economy, justice and politics. Any horizon in the development of being sought within the framework of transformation cannot be based on the infinite and unlimited process of exploitation of people and ecosystems.